Risk-aware decision making in the safety investments - Application of stochastic simulations and judgment value method. (January 2022) - Krasuski, Adam; Zimny, Mateusz; Hostikka, Simo; Makowski, Radosław
Abstract: We propose a methodology for risk-aware decision making related to the investment in safety. The methodology consists of probabilistic risk assessment and following cost-benefit analysis upon calculated risk values. We introduce a web-based tool for computing the risk for various safety regimes. The tool makes use of joint fire and evacuation modelling along with Monte Carlo sampling for uncertain or variate input variables. The results include individual as well as societal risk values, related to fatalities or serious injuries. The obtained changes in risk values – related to the applied safety measures – define an input for the cost-benefit analysis. The analysis is based on the Life Quality Index and J-value judgement method. As a case study, we used the hotel part of a seven-story mixed-use building. We designed the methodology to be applicable in day-to-day engineering calculations related to the safety of the building as well as other purposes, such as the introduction of the new product to the market. Therefore, in this article, we focus on the practical aspect of the methodology. Graphical abstract: Image 1 Highlights: ● A practical engineering tool for probabilistic fire risk assessment is presented. ● The tool is a web-based application with heavy rendering left on cloud or grid computing. ● The calculated risk is the subject of cost-benefit analysis based on the Life Quality Index approach. ● The approach allows one to relate the costs a given society spends for general safety with the fire safety investment at the level of a specific building. ● The method is complete and scalable, allowing day-to-day risk-aware decision making during the design process.